EM4 Effect on Macronutrients and Microbial Growth in Liquid Organic Fertilizer from Cibogo Market Waste - Dewi Widyabudiningsih; Kardian Rinaldi; Fachrel Muhammad Firdaus; Rafli Rizki Fauzi; Mentik Hulupi (Department of Chemical Engineering, Politeknik Negeri Bandung, 2025)
Waste represents a major environmental concern due to its contribution to pollution. According to the Ministry of Environment and Forestry, organic waste comprised 51.63% of total waste in Indonesia. This highlights the potential for converting organic waste into liquid organic fertilizer (LOF) through anaerobic fermentation. This study aimed to determine the relationship between macronutrient content and microbial growth in LOF and to determine the optimum fermentation time for producing LOF. LOF was made using organic waste from Cibogo market, including green vegetable waste and fruit peels banana, mango, and pineapple). The research was conducted using reactor which contained 5 kg of green vegetable waste and 5 kg of fruit peels, supplemented with EM4 bioactivator (200, 250, and 300 mL), water, and brown sugar. Samples were analyzed on days 0, 7, 14, 21, and 28. Chemical parameters measured included nitrogen, phosphorus, C-organic, and potassium content, and microbial analysis was conducted to determine the role of microorganisms in the fermentation process. Results showed that the optimal fermentation time for LOF production was seven days, corresponding to the peak concentrations of NPK and C-organic. However, further optimization of EM4 volume and the ratio between waste and bioactivator is required, since the nutrient levels remain below the recommended standard. Moreover, the correlation between microbial population and nutrient availability requires further research, particularly with respect to the quantity of EM4 applied.